2012
DOI: 10.1155/2012/819524
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring of the Physical and Chemical Properties of a Gasoline Engine Oil during Its Usage

Abstract: Physicochemical properties of a mineral-based gasoline engine oil have been monitored at 0, 500, 1000, 2000, 3500, 6000, 8500, and 11500 kilometer of operation. Tracing has been performed by inductively coupled plasma and some other techniques. At each series of measurements, the concentrations of twenty four elements as well as physical properties such as: viscosity at 40 and 100°C; viscosity index; flash point; pour point; specific gravity; color; total acid and base numbers; water content have been determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…There is no value specified for viscosity in the national standard of petroleum-/synthetic-based base oils. On the other hand, the viscosity of samples is similar to median value (30.7 mm 2 /s) of those measured in a set of 38 mineral base oils (min-max: 9.38-567 mm 2 /s) routinely used in the industry [20], and lower than the values measured for used motor oil in the literature [22]. The characteristic of viscosity data shed light on the underlying component of NTLs, which is base oils.…”
Section: Viscositysupporting
confidence: 76%
See 2 more Smart Citations
“…There is no value specified for viscosity in the national standard of petroleum-/synthetic-based base oils. On the other hand, the viscosity of samples is similar to median value (30.7 mm 2 /s) of those measured in a set of 38 mineral base oils (min-max: 9.38-567 mm 2 /s) routinely used in the industry [20], and lower than the values measured for used motor oil in the literature [22]. The characteristic of viscosity data shed light on the underlying component of NTLs, which is base oils.…”
Section: Viscositysupporting
confidence: 76%
“…Results also showed that 80% of samples comply with the national standard of petroleum-/synthetic-based base oils which holds N180°C as a limit value. The flash point of samples, on the other hand, is below the mean (243 ± 34°C) or median (234°C) value of those measured in a set of 38 mineral base oils (min-max: 178-314°C) routinely used in the industry [20], and lower than the values measured for used motor oil in the literature [22]. A notable variation in flash point may indicate the presence of solvent contamination or adulteration with light ends in fuels since additives with low flash points can lower the flash point of the fuel markedly to below that of the unadulterated product.…”
Section: Flash Pointmentioning
confidence: 55%
See 1 more Smart Citation
“…In this paper chemical modification by initial epoxidation of sunflower oil, followed by acetylation of epoxidized intermediate has been followed. This research is in continuing of our research on lubricants [24][25][26][27][28][29]. Economic considerations involve chemical modifications to be directed toward catalyst which could be applied at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently been involved in the investigation of lubricating oils [17][18][19][20][21][22]. In this paper we have performed an investigation on the relationship between flash points of some binary base oils and weight ratios of their components.…”
Section: Introductionmentioning
confidence: 99%